Genetic instability persists in non-neoplastic urothelial cells from patients with a history of urothelial cell carcinoma. - João Paulo de Castro Marcondes (Public Library of Science (PLoS), 2014)
Bladder cancer is one of the most common genitourinary neoplasms in industrialized countries. Multifocality and high recurrence rates are prominent clinical features of this disease and contribute to its high morbidity. Therefore, more sensitive and less invasive techniques could help identify individuals with asymptomatic disease. In this context, we used the micronucleus assay to evaluate whether cytogenetic alterations could be used as biomarkers for monitoring patients with a history of urothelial cell carcinoma (UCC). We determined the frequency of micronucleated urothelial cells (MNC) in exfoliated bladder cells from 105 patients with (n = 52) or without (n = 53) a history of UCC, all of whom tested negative for neoplasia by cytopathological and histopathological analyses. MNC frequencies were increased in patients with a history of UCC (non-smoker and smoker/ex-smoker patients vs non-smoker and smoker/ex-smoker controls; p<0.001), in non-smoker UCC patients (vs non-smoker controls; p<0.01), and in smoker/ex-smoker controls (vs non-smoker controls; p<0.001). Patients with a history of recurrent disease also demonstrated a higher MNC frequency compared to patients with non-recurrent neoplasia. However, logistic regression using smoking habits, age and gender as confounding factors did not confirm MNC frequency as a marker for UCC recurrence. Fluorescent in situ hybridization analysis (using a pan-centromeric probe) showed that micronuclei (MN) arose mainly from clastogenic events regardless of UCC and/or smoking histories. In conclusion, our results confirm previous indications that subjects with a history of UCC harbor genetically unstable cells in the bladder urothelium. Furthermore, these results support using the micronucleus assay as an important tool for monitoring patients with a history of UCC and tumor recurrence.